The Electrochemical Behavior of 1-Ethyl-3-Methyl Imidazolium Tetracyanoborate Visualized by In Situ X-ray Photoelectron Spectroscopy at the Negatively and Positively Polarized Micro-Mesoporous Carbon Electrode. Issue 13 (3rd November 2017) - Kruusma, Jaanus; Tõnisoo, Arvo; Pärna, Rainer; Nõmmiste, Ergo; Kuusik, Ivar; Vahtrus, Mikk; Tallo, Indrek; Romann, Tavo; Lust, Enn
Abstract : The electrochemical properties of the C(Mo2 C) | EMImB(CN)4 system have been analyzed using cyclic voltammetry, in situ X-ray photoelectron spectroscopy and electrochemical impedance spectroscopy techniques. The cyclic voltammetry and electrochemical impedance measurements indicated that the tetracyanoborate anions started to electrooxidize and electropolymerize at E = 2.12 V (vs. Ag/AgCl in EMImBF4 ). However, despite of the formation of compact dielectric polymer layer at the micro-mesoporous C(Mo2 C) electrode surface very slow electrochemical polymerization of tetracyanoborate anions continued further at E > 2.12 V leading to the blocking of the C(Mo2 C) electrode porous structure and to the reduction of the electrochemically active surface area necessary for the construction of the high energy density supercapacitors. Thus, the tetracyanoborate anion based ionic liquids can be used as the electrolytes for the initial formation of the passivating solid-electrolyte interface for the very wide cell potential supercapacitor positive electrodes, as an electrolyte additives for the solid-electrolyte interface formation or for the correction of the solid-electrolyte interface damages.